MPI implementations of Conways Game of Life and Kohomoto-Oono cellular automata - Anna Yur'evna Subbotina; Nikolai Igorevich Khokhlov (Компьютерные исследования и моделирование, 2010)
Results obtained during practical training session on MPI during high perfomance computing summer school MIPT-2010 are discussed. MPI technology were one of technologies proposed to participants for realization of project. 3D version of Conways Game of Life was proposed as a project. Algorithms used in the development, theoretical and practical assessment of their scalability is analyzed.